1999
DOI: 10.1251/bpo13
|View full text |Cite
|
Sign up to set email alerts
|

Role of a transbilayer pH gradient in the membrane fusion activity of the influenza virus hemagglutinin: Use of the R18 assay to monitor membrane merging

Abstract: It had been suggested that influenza virus-mediated membrane fusion might be dependent on a pH gradient across a target membrane. We have designed experiments in which this issue could be addressed. Two populations of liposomes were prepared, both simulating the plasma membrane of target cells, but with the pH of the internal aqueous medium buffered either at pH 7.4 (physiological cytosol pH) or at pH 5.0 (endosomal pH at which influenza virus displays maximal fusion activity). By monitoring fusion using the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…There is a pH gradient across many biological membranes, and it plays critical roles in cell functioning. Some roles of pH gradient include modulating bilayer asymmetry, , loading vesicles with charged species (i.e., amino acid, peptide, protein), controlling fusion processes, and maintaining degradative functions in acidic organelles . The pH gradient across a liposome membrane gives origin to a capacitive effect initially proposed by Ceh et al Later, the Hayes group observed that the electrophoretic mobilities of liposomes are affected by pH gradient across the liposomal membrane in the pH range 7.4−8.8 .…”
Section: Introductionmentioning
confidence: 99%
“…There is a pH gradient across many biological membranes, and it plays critical roles in cell functioning. Some roles of pH gradient include modulating bilayer asymmetry, , loading vesicles with charged species (i.e., amino acid, peptide, protein), controlling fusion processes, and maintaining degradative functions in acidic organelles . The pH gradient across a liposome membrane gives origin to a capacitive effect initially proposed by Ceh et al Later, the Hayes group observed that the electrophoretic mobilities of liposomes are affected by pH gradient across the liposomal membrane in the pH range 7.4−8.8 .…”
Section: Introductionmentioning
confidence: 99%